Propeller states in locally supercritical ULXs. Issue 2 (21st December 2022) - Middleton, M; Gúrpide, A; Walton, D J
ABSTRACT: An expected signature of the presence of neutron stars in the population of ultraluminous X-ray sources (ULXs) are large scale changes in X-ray luminosity, as systems reach spin equilibrium and a propeller state ensues. We explore the predicted luminosity changes when the disc is locally supercritical, finding that a significant parameter space in dipole field strength, and accretion rate (at large radius) can be accompanied by changes of less than an order of magnitude in luminosity. We discuss the spectral signature and locate three ULXs (IC 342 X-1, Cir ULX-5, and NGC 1313 X-1), which appear to show changes consistent with the super-Eddington systems entering a propeller state, and place rough constraints on the dipole field strength of NGC 1313 X-1 of < 10 10 G. This work implies that the most reliable means by which to search for putative propeller states will be to search for changes in hardness ratio and at high energies.